PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI RANTAI MAKANAN DI KELAS 5 SD NEGERI 34/I TERATAI - Gultom, Nova Indah; Septiwi, Ervina; Qomisatun, Prya Aprillia; Ervina, Rina (Jurnal Tunas Pendidikan, 2024)
This research was motivated by the low learning outcomes of science and science content for class V students at SD N 34/I Teratai. One solution to overcome this problem is to use the Problem Based Learning (PBL) learning model. The aim of this research is to determine the application of the Problem Based Learning (PBL) learning model to improve the science learning outcomes of class V students at SD N 34/I Teratai. This research method is Classroom Action Research (PTK) which is carried out in 2 cycles. Each cycle consists of 2 meetings and four stages, namely: planning, implementation, observation and reflection and the research time will be carried out in November 2023. The research subjects were 19 class V students, with 10 male students and 9 female students. Data collection techniques include observation and learning outcomes tests. The results of this research show that the science learning results in class V of SD N 34/I Teratai in the first cycle were classified as good. The learning outcomes of 12 students (63.1%) completed it while 7 students (36.8%) did not complete it. In cycle II it was classified as good with an increase in learning outcomes for 16 students (84.2%) and those whose completeness decreased to 3 students (15.75). Thus it can be concluded that using the Problem Based Learning (PBL) model can improve the learning outcomes of class V students at SD N 34/I Teratai.